Implementation of HOTS-based Instructions in Pesantren: A Case Study in Pondok Modern Tazakka Batang - As Shidqi, Hakim; Akbar, Rohul; Kuswoyo, Thony; Rokhib, Zainur; Musta'in, Muhamad Ari; Fahturohman, Arizal; Hidayat, Ferry (Universitas Islam Indonesia, 2024)
The development of Higher Order Thinking Skills (HOTS) in students at Islamic boarding schools (pesantren) is crucial due to their numerous advantages, such as the capacity to tackle social, scientific, and practical problems with effectiveness. Whether or not Pondok Modern Tazakka successfully integrated the use of HOTS questions in exams is the goal of this study. Through the application of descriptive phenomenological research methods and data collection techniques, including the tabulation of 132 test sheets in 44 subjects tested on KMI Class 6 students and interviews with 62 teachers in 8 subjects, it was discovered that 8 subjects exhibited no HOTS questions at all (19%), 6 subjects exhibited a decreasing number of HOTS questions (14%), 19 subjects exhibited a sharp increase in HOTS questions (45%), and 9 subjects exhibited a constant number of HOTS questions. The study's findings also demonstrate that, as long as supervisors (senior teachers) take a more proactive approach to giving junior teachers comprehensive training and ensure that all exam questions in each subject are HOTS exam questions, it is possible to guarantee that all exam questions will contain HOTS.